2020
DOI: 10.1017/s0033291720001567
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with heterogeneity of cognitive dysfunction in acute depression: a clustering approach

Abstract: Background Heterogeneity in cognitive functioning among major depressive disorder (MDD) patients could have been the reason for the small-to-moderate differences reported so far when it is compared to other psychiatric conditions or to healthy controls. Additionally, most of these studies did not take into account clinical and sociodemographic characteristics that could have played a relevant role in cognitive variability. This study aims to identify empirical clusters based on cognitive, clinical and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
(60 reference statements)
2
6
0
Order By: Relevance
“…Between-profile differences were large in terms of both occupational depression and cognitive performance, as indexed by Cohen's ds ≥ 1.263. Such effect sizes are consistent with those found in clusteranalytic research pertaining to neuropsychological functioning in clinical depression (Vicent-Gil et al, 2020). Our findings underline the utility of combining variable-and person-centered approaches in depression research.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Between-profile differences were large in terms of both occupational depression and cognitive performance, as indexed by Cohen's ds ≥ 1.263. Such effect sizes are consistent with those found in clusteranalytic research pertaining to neuropsychological functioning in clinical depression (Vicent-Gil et al, 2020). Our findings underline the utility of combining variable-and person-centered approaches in depression research.…”
Section: Discussionsupporting
confidence: 88%
“…The second cluster (Cluster 2; n = 145) involved individuals with relatively high ODI scores ( M = 2.172, SD = 0.407) and relatively low cognitive performance ( M = 0.226, SD = 0.209). The model showed a satisfactory fit, with a Silhouette coefficient of 0.4 ( Vicent-Gil et al, 2020 ). Welch’s ANOVAs revealed that the two clusters differed substantially from one another in terms of both ODI scores, a F (1, 218.360) = 1083.277, p < 0.001, Cohen’s d = 2.492, and cognitive performance, a F (1, 213.427) = 269.956, p < 0.001, Cohen’s d = 1.263.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, in a healthy student sample Vervaeke et al (2020) observed emotional transfer for self-reported anxiety levels, in absence of effects of CCT on RNT or depressive symptomatology. Such inconsistencies may at least partially be due to sample heterogeneity (e.g., community samples, MDD/RMD patients), where strong individual differences have been observed in terms of baseline features (e.g., cognitive impairments; Pu et al, 2018 ; Vicent-Gil et al, 2020 ) and treatment response (e.g., Hoorelbeke et al, 2021 ). Individual differences may be distinct from other factors contributing to variation across studies such as differences in administration modality (lab vs. internet), number of required sessions (varies from 1 to 10 in the literature), software versions (e.g., lab versions typically use multiple training tasks whereas internet protocols have used a single task), and demand characteristics (e.g., high variability in the level of reimbursement for participation across studies).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive recovery can improve overall outcomes ( 24 ). However, heterogeneity regarding cognitive impairment has been mentioned in patients with MDD, in particular executive functions ( 25 , 26 ). One study revealed that some medication-free depressed individuals showed significant reductions in executive function ( 27 ), whereas others showed subtle or no executive function deficits ( 26 , 28 ).…”
Section: Introductionmentioning
confidence: 99%